2007
DOI: 10.1177/1420326x07078854
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Sustainable Management of Urban Storm-Water

Abstract: Despite the development of urban drainage systems over the past 5000 years, there are still many challenges to their effective use. There are growing demands with respect to runoff quantity and quality, visual amenity (landscape aesthetics), protection of ecology and beneficial water uses and interaction with the operation of existing municipal wastewater systems. Current solutions that rely mainly on pipe networks may not be sustainable, especially in developing countries. By considering the driving forces in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
75
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(81 citation statements)
references
References 15 publications
0
75
0
6
Order By: Relevance
“…In the latter we assume that the design of the drainage system is updated to match the degree of urban development in the period 1984-2014 (2013-2015), as well as the projected intensity of extreme precipitation towards the end of this century (2081-2100) for representative concentration pathways (RCP) RCP 4.5 and RCP 8.5 (Meinshausen et al, 2011), respectively. This is based on the notion that urban drainage systems are often developed in parallel to (planned) urban development and in some cases, are based on the future projections of precipitation from climate models (Chocat et al, 2007;Arnbjerg-Nielsen, 2011;Gregersen et al, 2014). This allows us to examine quantitatively the efficiency of expanding the urban drainage system, which is currently the most common large-scale adaptation measure in protecting urban areas from pluvial flooding.…”
Section: Frameworkmentioning
confidence: 99%
“…In the latter we assume that the design of the drainage system is updated to match the degree of urban development in the period 1984-2014 (2013-2015), as well as the projected intensity of extreme precipitation towards the end of this century (2081-2100) for representative concentration pathways (RCP) RCP 4.5 and RCP 8.5 (Meinshausen et al, 2011), respectively. This is based on the notion that urban drainage systems are often developed in parallel to (planned) urban development and in some cases, are based on the future projections of precipitation from climate models (Chocat et al, 2007;Arnbjerg-Nielsen, 2011;Gregersen et al, 2014). This allows us to examine quantitatively the efficiency of expanding the urban drainage system, which is currently the most common large-scale adaptation measure in protecting urban areas from pluvial flooding.…”
Section: Frameworkmentioning
confidence: 99%
“…Traditional stormwater 41 management technology in the form of sewers is installed with the aim of draining 42 stormwater efficiently to protect human health and human assets, but this practice often 43 disturbs the natural water cycle and has a multitude of other detrimental environmental 44 impacts (Schuster et al, 2005). Alternative stormwater management has gained 45 increased attention in recent years due to different drivers such as aging infrastructure, a 46 wish for more cyclical rather than linear systems (Chocat et al, 2007), and increases in 47 size and occurrence of extreme rainfall due to anthropogenic climatic changes 48 (Arnbjerg-Nielsen et al, 2013). A suite of newer structural and non-structural practices 49 for stormwater management has emerged, reflecting the different perspectives involved 50 and the needs for driving the stormwater profession in new directions.…”
Section: Introduction 39mentioning
confidence: 99%
“…In Copenhagen, Melbourne and several other cities around the world it is attempted to use green and sustainable stormwater technologies to solve the experienced problems of the urban water cycle (Chocat et al, 2007(Chocat et al, , 2001Mitchell, 2006). Fletcher et al, (2015) suggested the term Stormwater Control Measures (SCM) to encompass the wide variety of global terminology encompassing these solutions, which is still evolving and now includes "Nature-based solutions" in Europe (Kabisch et al, 2016) and the "Sponge city" concept in China (Gaines, 2016).…”
Section: Introductionmentioning
confidence: 99%